LIVING WITH OUR DREAMS - Bloom, Leonard (PINS-Psychology in Society, 2025)
Kruger, D (2005) Dreams and how to understand them. Cape Town: Double Storey Books. ISBN 177013 037 3. Pages xii + 113. Dreyer Kruger’s concise book is a welcome addition to the books by South Africans that are addressed to our problems and conditions. It is, moreover, more enlightening and humane than many more conventional texts. Kruger is one of South Africa’s veteran psychologists, and one whose humanist-phenomenological perspective is sadly missing from most psychological teaching and practice.